Study of the influence of consumer trust factors and the marketing mix on consumer value and consumer loyalty - Burakhanova, A.K.; Bayzhaksynova, G.K.; Orazgaliyeva, E.B.; Skorobogatykh, I.I. (BUKETOV BUSINESS REVIEW, 2024)
Object: The aim of the study is to determine the importance of consumer trust in value creation and to study how consumer trust influences their purchase decision and consumer loyalty. Methods: As it is shown in the scientific literature, several methods are used when writing a research paper, which are classified as field and desk, quantitative and qualitative. Typically, one or both of these may be used in a study. Depending on the purpose of our work in our study, at the first stage, we analyzed second-order information based on desk research. It was used to review scientific articles relevant to the topic of a previously published study. At the second stage of the study, we conducted an opinion poll using the method of quantitative research. The survey was conducted on the basis of a conceptual model and measuring scales of previous studies. To test the questionnaire developed for the survey, a pilot survey was organized for 40 respondents. To get answers to questions about who was conducted in research, how many of them should be, and how to se lect them, we conducted a selection using sources of scientific literature. Findings: The value of the study is specific, the significance of the work lies in the fact that our study considers the chain of consumer value creation in the production and sale of food products and involves the measurement of con sumer value in this chain based on factors that form consumer beliefs. In this regard, it complements the studies carried out so far on the problem of creating customer value. Conclusions: The results of the study can be considered when forming a chain of consumer value creation in the marketing activities of sausage manufacturers.